2007
DOI: 10.1902/jop.2007.060491
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Periodontitis and Diabetes: Lessons From Rodent Studies

Abstract: Findings from rodent studies have been useful in increasing our understanding of periodontitis, diabetes, and their association and hold great promise for future investigations given the wide variety of possibilities for testing biologic hypotheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 142 publications
(315 reference statements)
1
30
0
1
Order By: Relevance
“…[36] The association between diabetes mellitus and periodontal disease is therefore, considered to be bidirectional: diabetes as a risk factor for periodontitis and periodontitis as a possible severity for diabetes. In fact, aggressive periodontitis is recognized as the sixth serious complication of diabetes.…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…[36] The association between diabetes mellitus and periodontal disease is therefore, considered to be bidirectional: diabetes as a risk factor for periodontitis and periodontitis as a possible severity for diabetes. In fact, aggressive periodontitis is recognized as the sixth serious complication of diabetes.…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…Experimental PD in rats is based upon subgingival placement of ligatures that facilitate accumulation of bacteria, which in turn initiate periodontal inflammation (Graves, Fine, Teng, Van Dyke, & Hajishengallis, 2008; Pontes Andersen et al, 2007). Thus, subgingival placement of the ligature increases biofilm formation, and a direct comparison between ligature‐induced PD in rats and naturally occurring PD in humans is not possible (Graves et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, standardized animal models with controlled diet, housing and microbial sampling may be preferable for these studies (Kaye, 2012), which is why rat models with ligature‐induced PD have been used frequently. Animal models with both T2D and PD have increased inflammatory cytokine responses, elevated oxidative stress, raised AGE levels, altered glucose metabolism, and increased severity of PD (Pontes Andersen, Flyvbjerg, Buschard, & Holmstrup, 2007). In addition to being a local irritant, the ligature serves as a reservoir for bacteria, which mediates periodontal tissue destruction (Bjornsson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An explanation in this regard may be derived from the fact that periodontal disease elevates the systemic burden of infl ammatory mediators (such as CRP) that aggravate the existing metabolic disorder in patients with chronic hyperglycemia [9,10], however, SRP reduces the severity of periodontal infection and decreases the systemic burden of infl ammatory mediators which in turn reduces the hyperglycemic state in prediabetic patients. An interesting fi nding in the present study was that despite reduction in the severity of periodontal infl ammation in both groups compared to baseline values, FBG levels in both groups remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies [4,[6][7][8] have shown that prediabetic patients (patients with impaired glucose tolerance) are also susceptible to periodontal destruction as compared to their systemically healthy controls. It has been proposed that local periodontal infection increases the systemic burden of infl ammatory mediators (such as C-reactive protein [CRP]), which in turn aggravate the existing metabolic disorder in hyperglycemic patients [9,10]. Additionally, increased production and accumulation of advanced glycation endproducts in periodontal tissues raised cellular oxidative stress and production and accumulation of proinfl ammatory cytokines (such as interleukin (IL)-6, IL-1β, IL-18, matrix metalloproteinase [MMP]-8, and MMP-9) in the serum, saliva, and gingival crevicular fl uid of patients with persistent hyperglycemia tend to worsen periodontal infl ammation [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%